Comprehensive review on Matricaria pubescens: traditional uses, chemical composition, and pharmacological potential - Elhasnaoui Abdelhadi; Janah Iman; Ait Tastift Maroua; El-Haidani Ahmed; Lahrach Nadia (Scientific African, 2025)
Matricaria pubescens (Desf.) Sch.Bip., commonly known as ''El Ouazouaza,'' is a medicinal plant from the Asteraceae family, predominantly found in the arid and semi-arid regions. It has long been valued in traditional medicine for its therapeutic potential in treating digestive, respiratory, and infectious diseases. This comprehensive review consolidates existing knowledge on M. pubescens, emphasizing its traditional uses, phytochemical composition, and pharmacological properties. Phytochemical investigations have revealed that M. pubescens is rich in secondary metabolites, particularly flavonoids, coumarins, and essential oils, which exhibit diverse chemical profiles. Pharmacological studies have demonstrated its antibacterial, antioxidant, anti-inflammatory, antihypertensive, and antivenom activities, supporting its traditional medicinal applications. These bioactive properties make M. pubescens a promising candidate for pharmaceutical and therapeutic development. Despite its well-documented ethnopharmacological significance, further in-depth pharmacological and clinical studies are required to validate its efficacy, determine its safety profile, and optimize its medicinal applications. Such investigations will facilitate its integration into modern medicine while ensuring its sustainable use.